Development and Testing of the Texas Christian University Criminal Thinking Scales 3.0 - Sease, Thomas (Crime & delinquency, 2023)
Criminal thinking patterns?attitudes, beliefs, or values supportive of criminal behavior?represent modifiable clinical targets that can be influenced during treatment as a way of decreasing clients? risk for recidivism. This study developed a revised measure of criminal thinking based on the Texas Christian University Criminal Thinking Scales (TCU CTS). Using a sample of 797 people, results showed the revised instrument (TCU CTS 3.0) measured criminal thinking in five key areas: (1) Power Orientation, (2) Justification, (3) Insensitivity to Impact of Crime, (4) Grandiosity, and (5) Response Disinhibition. Confirmatory factor analysis showed the 5-factor solution reasonably fit the data and measurement invariance was achieved for assigned sex at birth and race. Implications and future directions are discussed.